What do the contrasting views of Harries and Eisenman add to architectural culture in bringing aesthetic impressions back to the built environment? - Paul, Abhijit; Sinha, Kshitij (Journal of Architecture and Urbanism, 2024)
In the era of modernism, the natural symbols of art – expressed through aesthetic elements – have been seen replaced by the verbal notations of communication. The replacement forced the postmodernists to deconstruct the concept of modernism to bring back the notion of symbolic art superficially and to revitalize the meaning of art and its cohesive presence in the built environment. The revitalization process, however, does not seem to have gone without raising questions in the academic community. Does the aesthetic impulse come from the structural spirit of a built form alone? Is just aesthetics deeply rooted in built-form identity? Is aesthetics not associated with the social environment and economic living? Can aesthetics exist in isolation? Can aesthetics be more of a by-product of functionality than the product itself? Using the works of Harries and Eisenman, the paper develops a review sketch exploring these questions. Many other attributes, such as aesthetics production, aesthetics generation, and environmental aesthetics, and their roles in art appreciation have ensured positions in the discussion. The conclusions seem to warn that the influence of social co-existence in defining built-form aesthetics in the postmodern era and later, divorced from reality – avoiding the presence of the different layers in the social fabric and their relationships among themselves – seldom helps to produce any futuristic vision but invites chaos in thoughts and perceptions crossing over between studies and practices in architecture.